HIV-1 Transmitted Drug Resistance Mutations in Newly Diagnosed Antiretroviral-Naive Patients in Turkey - KORTEN, VOLKAN (MARY ANN LIEBERT, INC, 2016)
HIV-1 replication is rapid and highly error-prone. Transmission of a drug-resistant HIV-1 strain is possible and occurs within the HIV-1-infected population. In this study, we aimed to determine the prevalence of transmitted drug resistance mutations (TDRMs) in 1,306 newly diagnosed untreated HIV-1-infected patients from 21 cities across six regions of Turkey between 2010 and 2015. TDRMs were identified according to the criteria provided by the World Health Organization's 2009 list of surveillance drug resistance mutations. The HIV-1 TDRM prevalence was 10.1% (133/1,306) in Turkey. Primary drug resistance mutations (K65R, M184V) and thymidine analogue-associated mutations (TAMs) were evaluated together as nucleos(t)ide reverse transcriptase inhibitor (NRTI) mutations. NRTI TDRMs were found in 8.1% (107/1,306) of patients. However, TAMs were divided into three categories and M41L, L210W, and T215Y mutations were found for TAM1 in 97 (7.4%) patients, D67N, K70R, K219E/Q/N/R, T215F, and T215C/D/S mutations were detected for TAM2 in 52 (3.9%) patients, and M41L + K219N and M41L + T215C/D/S mutations were detected for the TAM1 + TAM2 profile in 22 (1.7%) patients, respectively. Nonnucleoside reverse transcriptase inhibitor-associated TDRMs were detected in 3.3% (44/1,306) of patients (L100I, K101E/P, K103N/S, V179F, Y188H/L/M, Y181I/C, and G190A/E/S) and TDRMs to protease inhibitors were detected in 2.3% (30/1,306) of patients (M46L, I50V, I54V, Q58E, L76V, V82A/C/L/T, N83D, I84V, and L90M). In conclusion, long-term and large-scale monitoring of regional levels of HIV-1 TDRMs informs treatment guidelines and provides feedback on the success of HIV-1 prevention and treatment efforts.
Keywords: HIV-1-INFECTED PERSONS; SURVEILLANCE; THERAPY; RECOMMENDATIONS; EPIDEMIOLOGY; UPDATE